Fluid‐Driven Tensile Fracture and Fracture Toughness in Nash Point Shale at Elevated Pressure. Issue 2 (15th February 2020) - Gehne, S.; Forbes Inskip, N. D.; Benson, Philip M.; Meredith, P. G.; Koor, N.
Abstract: A number of key processes, both natural and anthropogenic, involve the fracture of rocks subjected to tensile stress, including vein growth and mineralization, and the extraction of hydrocarbons through hydraulic fracturing. In each case, the fundamental material property of mode‐I fracture toughness must be overcome in order for a tensile fracture to propagate. While measuring this parameter is relatively straightforward at ambient pressure, estimating fracture toughness of rocks at depth, where they experience confining pressure, is technically challenging. Here we report a new analysis that combines results from thick‐walled cylinder burst tests with quantitative acoustic emission to estimate the mode‐I fracture toughness ( K Ic ) of Nash Point Shale at confining pressure simulating in situ conditions to approximately 1‐km depth. In the most favorable orientation, the pressure required to fracture the rock shell (injection pressure, P inj ) increases from 6.1 MPa at 2.2‐MPa confining pressure ( P c ), to 34 MPa at 20‐MPa confining pressure. When fractures are forced to cross the shale bedding, the required injection pressures are 30.3 MPa (at P c = 4.5 MPa) and 58 MPa ( P c = 20 MPa), respectively. Applying the model of Abou‐Sayed et al. (1978, https://doi.org/10.1029/JB083iB06p02851) to estimate the initial flaw size, we calculate that this pressure increase equates to an increase in K Ic from 0.36 to 4.05 MPa·m 1/2 as differential fluid pressure ( P inj − P c ) increases from 3.2 to 22.0 MPa. We conclude that the increasing pressure due to depth in the Earth will have a significant influence on fracture toughness, which is also a function of the inherent anisotropy. Key Points: Fracture toughness of an anisotropic shale is calculated using direct fluid pressurization and tensile fracture growth Our data suggest that fracture toughness maintains a consistent value as pressure‐driven cracks extend across the sample Fracture toughness increases with confining pressure and is noticeably higher for fractures crossing bedding planes (Divider orientation) than for those parallel to bedding (Short‐Transverse orientation)